Grandpa's great escape - Walliams, David 1971- (HarperCollins Children's Books, 2017)
Jack's Grandpa wears his slippers to the supermarket serves up Spam à la Custard for dinner and often doesn't remember Jack's name, but he can still take to the skies in a speeding spitfire and save the day. An exquisite portrait of the bond between a small boy and his beloved Grandpa this book takes readers on an incredible journey with spitfires over London and great escapes through the city in a high octane adventure full of comedy and heart. Illustrated by the award-winning Tony Ross